2009
DOI: 10.1038/nm.1974
|View full text |Cite
|
Sign up to set email alerts
|

Effective, low-titer antibody protection against low-dose repeated mucosal SHIV challenge in macaques

Abstract: Neutralizing antibodies are thought crucial to HIV vaccine protection but a major hurdle is the high antibody concentrations likely required as suggested by studies in animal models1. However, these studies typically apply a large virus inoculum to ensure infection in control animals in single challenge experiments. In contrast, most human infection via sexual encounter probably involves repeated exposures to much lower doses of virus2–4. Therefore, animal studies may have overestimated protective antibody lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
428
4
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 507 publications
(451 citation statements)
references
References 36 publications
12
428
4
3
Order By: Relevance
“…This view has been reinforced by recent studies showing that HIV-1 infection can be limited or even prevented in animals with a wide range of functional antibody titers as measured by in vitro neutralization assays when these antibodies are continuously present, as would be the case for vaccine-induced immunity (31,37,38).…”
Section: Discussionmentioning
confidence: 97%
“…This view has been reinforced by recent studies showing that HIV-1 infection can be limited or even prevented in animals with a wide range of functional antibody titers as measured by in vitro neutralization assays when these antibodies are continuously present, as would be the case for vaccine-induced immunity (31,37,38).…”
Section: Discussionmentioning
confidence: 97%
“…Notwithstanding the modest efficacy of the RV144 Thai trial in humans (1) that correlated binding Abs with a lower risk of infection, much of the HIV-1 vaccine research focus has been directed toward developing strategies and immunogens that will elicit protective Abs, including broadly neutralizing Abs (bNAbs). This goal is supported by the overwhelming evidence of the capability of broadly neutralizing mAbs (bNmAbs) given prior to mucosal exposure in preventing viral infection in macaques using the chimeric simian/HIV (SHIV) bearing HIV env (2)(3)(4)(5). Neutralizing polyclonal Igs at high concentrations can block infection and have been shown to ameliorate disease pathogenesis in nonhuman primates (NHP) (6,7).…”
mentioning
confidence: 99%
“…Indeed, a recent multinational study of potential PrEP users showed that route of administration was the most important attribute regarding acceptability of a PrEP program, with a monthly or bimonthly injection preferred over daily or intermittent pills (17). In addition, numerous studies in macaques have demonstrated that passive immunization with bNAbs can prevent infection by hybrid simian-human immunodeficiency viruses (18)(19)(20)(21). Until recently, however, such an approach was considered infeasible owing to the limited potency and/or breadth of the available bNAbs, such as 2F5, 4E10, and 2G12 (22,23).…”
mentioning
confidence: 99%